1 Thessalonians 2:14-16 and the Church in Jerusalem - Bockmuehl, Markus (Tyndale bulletin, 2001)
Decades of interpretative controversy have failed to provide a satisfactory explanation of what Judaean events, if any, might have occasioned St Paul’s bitter invective in 1 Thessalonians 2:14-16. After re-examining the familiar arguments by B.A. Pearson and others for a non-Pauline interpolation, this study questions the widespread assumption that Jewish persecution of Christians cannot be substantiated prior to the first Jewish War. Rehearsing the evidence for hostile measures against Jewish believers c. AD 36 and again under Agrippa I in 41/42, the argument turns to the neglected suggestion by the sixth-century chronicler Malalas of Antioch that a further persecution of the Jerusalem church took place ‘in the eighth year of Claudius’ (AD 48/49). Such a course of events during the notorious procuratorship of Ventidius Cumanus would shed light not only on 1 Thessalonians 2, but possibly also on the setting of Galatians. In any case, both Josephus and rabbinic literature indicate that the death of Agrippa I was widely perceived as the beginning of a disastrous downturn in Jewish fortunes, to which Paul may be alluding in v. 17. Ironically, a number of these points were familiar to scholars in the 18th and 19th centuries, but seem since then to have been forgotten.